Fitness of calves born from in vitro-produced fresh and cryopreserved embryos - Gómez, Enrique; Murillo, Antonio; Carrocera, Susana; Pérez-Jánez, Juan José; Benedito, Jose Luis; Martín-González, David; Gimeno, Isabel (Frontiers in Veterinary Science, 2022)
In cattle, vitrification/warming (V/W) and freezing/thawing (F/T) differently affect the physiology and survival of in vitro produced (IVP) embryos. In this study we analyzed the effects of both cryopreservation techniques on the offspring. IVP embryos cultured with albumin and with or w/o 0.1% serum until Day-6, and thereafter in single culture w/o protein, were transferred on Day-7 after F/T, V/W or as fresh, resulting in N=24, 14 and 13 calves, respectively. Calves were clinically examined at birth, and blood analyzed before and after colostrum intake (Day-0), and subsequently on Day-15 and Day-30. On Day-0, both V/W and F/T increased creatinine and capillary refill time (CRT), and reduced heart beats in calves. F/T showed lower PCO2, hemoglobin and packed cell volume than V/W, while V/W increased Na+ levels. Colostrum effects were not affected by cryopreservation, indicating similar adaptive ability among fresh and cryopreserved calves, although PCO2 did not decrease in V/W calves after colostrum intake. Serum in culture affected (P<0.05) calf temperature, CRT, HCO3–, Base Excess (BE), TCO2, creatinine, urea and anion gap. On Day-15, the effects of cryopreservation disappeared. In contrast, Day-30 values were influenced by diarrhea appearance, mainly in V/W calves (i.e., lower values of TCO2, HCO3–, and BE; and increased glucose, anion gap, and lactate), although with no more clinical compromise than fresh and F/T calves. Diarrhea affected PCO2 and Na+ in all groups. Embryo cryopreservation, and/or culture, yield metabolically different calves, including effects on protein and acid-base metabolism, and perhaps compromised immune status as shown by unequal diarrhea incidence.